2010
DOI: 10.1073/pnas.1009669107
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation mediated by the Arabidopsis homolog of PRMT5 is essential for proper pre-mRNA splicing

Abstract: Protein arginine methylation, one of the most abundant and important posttranslational modifications, is involved in a multitude of biological processes in eukaryotes, such as transcriptional regulation and RNA processing. Symmetric arginine dimethylation is required for snRNP biogenesis and is assumed to be essential for pre-mRNA splicing; however, except for in vitro evidence, whether it affects splicing in vivo remains elusive. Mutation in an Arabidopsis symmetric arginine dimethyltransferase, AtPRMT5, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
185
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(191 citation statements)
references
References 51 publications
5
185
1
Order By: Relevance
“…pTAC12 might be a key component of the phytochrome signaling pathway to regulate PEP activity and plastid gene expression. Protein methylation is involved in multiple biological processes, such as transcriptional regulation and RNA processing (Deng et al, 2010). pTAC14 is a member of the class VII subgroup of the SET family, with a truncated SET domain and a Rubisco LSMT substratebinding domain (Ng et al, 2007; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…pTAC12 might be a key component of the phytochrome signaling pathway to regulate PEP activity and plastid gene expression. Protein methylation is involved in multiple biological processes, such as transcriptional regulation and RNA processing (Deng et al, 2010). pTAC14 is a member of the class VII subgroup of the SET family, with a truncated SET domain and a Rubisco LSMT substratebinding domain (Ng et al, 2007; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While regulated splicing networks as basis of fundamental biological programs have so far not been characterized in plants, numerous studies supported the occurrence of specific AS patterns linked to certain tissues, development, and stress responses in plants (Palusa et al, 2007;Simpson et al, 2008;Filichkin et al, 2010;Zenoni et al, 2010). Furthermore, important roles of AS control in the regulation of the circadian clock (Sanchez et al, 2010;Staiger and Green, 2011;James et al, 2012) and flowering time (Deng et al, 2010) have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…Single-end 86-nucleotide RNA-seq reads were aligned to the TIGR6.1 genome sequences using TopHat 49 . Uniquely mapped reads were used for subsequent analysis 50 .…”
Section: Subcellular Localizationmentioning
confidence: 99%